2021
DOI: 10.7759/cureus.18557
|View full text |Cite
|
Sign up to set email alerts
|

Does Fecal-Oral Transmission of SARS-CoV-2 Due to Low Sanitation Conditions Contribute to Low Mortality Rates From COVID-19

Abstract: Background: The novel coronavirus disease 2019 (COVID-19) is a global pandemic generated by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The primary infection site is mucosal surfaces, mainly the lungs and the intestine, where epithelial cells can be infected. COVID-19 has spread throughout the world, causing millions of deaths and hundreds of millions of confirmed infections. Despite the global spread of SARS-CoV-2, there are extreme differences between countries in mortality rates and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Epidemiological studies suggested fecal-oro transmission in cases such as the Diamond Princess cruise ship, where at least 20% of passengers were confirmed to be infected with SARSCoV-2, plausibly as the result of a superspreading event not implying person-to-person transmission [ 165 ].…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies suggested fecal-oro transmission in cases such as the Diamond Princess cruise ship, where at least 20% of passengers were confirmed to be infected with SARSCoV-2, plausibly as the result of a superspreading event not implying person-to-person transmission [ 165 ].…”
Section: Methodsmentioning
confidence: 99%